Charge Transfer Complexes Between Some Polar Solvents and π-Acceptors - M. Ghobrial, Nadia (Asian Journal of Chemistry, 2010)
The charge-transfer complexes formed by a number of π-acceptors with dimethylsulphoxidc, dimethylformamide and tetrahydrofuran have been measured in methylene chloride at 25ºC. Transition energies of these complexes as well as ionization potentials of the π-donors have been determined. All CT complexes studied have a 1 : 1 stoichiometry. Solvent effect on the electronic transition of the CT have been presented and discussed.